2022
DOI: 10.3389/fpls.2022.955843
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing photosynthesis to produce electricity using cyanobacteria, green algae, seaweeds and plants

Abstract: The conversion of solar energy into electrical current by photosynthetic organisms has the potential to produce clean energy. Life on earth depends on photosynthesis, the major mechanism for biological conversion of light energy into chemical energy. Indeed, billions of years of evolution and adaptation to extreme environmental habitats have resulted in highly efficient light-harvesting and photochemical systems in the photosynthetic organisms that can be found in almost every ecological habitat of our world. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 101 publications
1
39
0
Order By: Relevance
“…In our previous studies, ,, we showed that the source of the electrons harvested in BPECs from the water oxidation reaction performed by PSII. The addition of DCMU to the organisms was shown to inhibit photocurrent production in BPECs based on microalgae, seaweeds, and plants, indicating that DCMU penetrates into the chloroplasts and binds to PSII.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…In our previous studies, ,, we showed that the source of the electrons harvested in BPECs from the water oxidation reaction performed by PSII. The addition of DCMU to the organisms was shown to inhibit photocurrent production in BPECs based on microalgae, seaweeds, and plants, indicating that DCMU penetrates into the chloroplasts and binds to PSII.…”
Section: Resultsmentioning
confidence: 95%
“…The results display accumulation of 0.3 and 0.175 μmol H 2 in light and dark operated BPEC, in a good correlation with the current formation. The Faradaic efficiency for the hydrogen production in dark and light was calculated as the ratio between the total current production divided by the number of In our previous studies, 23,26,27 we showed that the source of the electrons harvested in BPECs from the water oxidation reaction performed by PSII. The addition of DCMU to the organisms was shown to inhibit photocurrent production in BPECs based on microalgae, seaweeds, and plants, indicating that DCMU penetrates into the chloroplasts and binds to PSII.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was reported that bio-photo electrochemical cells (BPECs) are not limited to micro-organisms and can be based on photosynthetic macroorganisms such as seaweeds [ 27 ] and aqueous and terrestrial plants [ 28 ] as electron donors. Interestingly, macroorganisms-based BPECs have produced an electrical current in both dark and light that was about 100–1000 times greater than photosynthetic microorganisms [ 29 ]. Rather than using whole microorganisms in BECs, electrical current can be produced via photon excitation by utilization of isolated photosynthetic components in different levels of purification, such as Thylakoid membranes [ 22 ], Chloroplasts [ 30 ], and Photosystems [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%